Extracting autism spectrum disorder data from the electronic health record - Bush, Ruth A.; Connelly, Cynthia D.; Pérez, Alexa; Barlow, Halsey; Chiang, George J. (Applied Clinical Informatics, 2017)
Background: Little is known about the health care utilization patterns of individuals with pediatric autism spectrum disorder (ASD).Objectives: Electronic health record (EHR) data provide an opportunity to study medical utilization and track outcomes among children with ASD.Methods: Using a pediatric, tertiary, academic hospital’s Epic EHR, search queries were built to identify individuals aged 2–18 with International Classification of Diseases, Ninth Revision (ICD-9) codes, 299.00, 299.10, and 299.80 in their records. Codes were entered in the EHR using four different workflows: (1) during an ambulatory visit, (2) abstracted by Health Information Management (HIM) for an encounter, (3) recorded on the patient problem list, or (4) added as a chief complaint during an Emergency Department visit. Once individuals were identified, demographics, scheduling, procedures, and prescribed medications were extracted for all patient-related encounters for the period October 2010 through September 2012.Results: There were 100,000 encounters for more than 4,800 unique individuals. Individuals were most frequently identified with an HIM abstracted code (82.6%) and least likely to be identified by a chief complaint (45.8%). Categorical frequency for reported race (2 = 816.5, p < 0.001); payor type (2 = 354.1, p < 0.001); encounter type (2 = 1497.0, p < 0.001); and department (2 = 3722.8, p < 0.001) differed by search query. Challenges encountered included, locating available discrete data elements and missing data.Conclusions: This study identifies challenges inherent in designing inclusive algorithms for identifying individuals with ASD and demonstrates the utility of employing multiple extractions to improve the completeness and quality of EHR data when conducting research.Citation: Bush RA, Connelly CD, Pérez A, Barlow H, Chiang GJ. Extracting autism spectrum disorder data from the electronic health record. Appl Clin Inform 2017; 8: 731–741 https://doi.org/10.4338/ACI-2017-02-RA-0029
Keywords: Autism spectrum disorder; comparative effectiveness research; electronic health record; pediatrics